The Relationship Between Civil Society Movements and Political Parties In The Legal Politics Of Legislation In Indonesia - Mahendra, Sandya (Jurnal Hukum Replik, 2025)
Public participation in the formulation of laws and regulations constitutes a crucial element in realizing the principles of a democratic rule of law in Indonesia. Although regulatory frameworks such as Law No. 12 of 2011 guarantee the principle of openness and the right of citizens to engage in the legislative process, practical implementation often reveals that public participation remains largely procedural and fails to meaningfully influence substantive decision-making. This study aims to elaborate on the concept of meaningful participation within the legislative framework and to analyze the relational model between civil society movements and political parties in Indonesia’s legislative process. The research employs an empirical legal methodology, utilizing statutory, conceptual, and sociological approaches. The findings indicate that the relationship between civil society movements and political parties in Indonesia’s legislative process is complex and heterogeneous, depending on political context, advocacy issues, and the power as well as strategies of the actors involved. On one hand, collaborative relations may emerge when shared visions and interests exist—such as in the enactment of the Law on the Crime of Sexual Violence (UU TPKS) and the Law on Personal Data Protection (UU PDP)—where public participation has positively influenced policy substance. On the other hand, confrontational relations often arise when political parties disregard civil society aspirations, as observed in the legislative processes of the Omnibus Law on Job Creation and the revision of the Military Law, both of which were marked by limited transparency and minimal public dialogue.